The Early Evolution of Rhynchosaurs - Ezcurra, Martín D.; Montefeltro, Felipe; Butler, Richard J. (Frontiers in Ecology and Evolution, 2016)
The rhynchosaurian archosauromorphs are an important and diverse group of fossil tetrapods that first appeared during the Early Triassic and probably became extinct during the early Late Triassic (early Norian). Here, the early evolution of rhynchosaurs during the Early and early Middle Triassic (Induan−Anisian: 252.2−242 Mya) is reviewed based on new anatomical observations and the implications of these observations for the taxonomy, phylogenetic relationships and macroevolutionary history of the group. A quantitative phylogenetic analysis recovered a paraphyletic genus Rhynchosaurus, with “Rhynchosaurus” brodiei more closely related to hyperodapedontines than to Rhynchosaurus articeps. Therefore, a new genus is erected, resulting in the new combination Langeronyx brodiei. A body size analysis found two independent increases in size in the evolutionary history of rhynchosaurs, one among stenaulorhynchines and the other in the hyperodapedontine lineage. Maximum likelihood fitting of phenotypic evolution models to body size data found ambiguous results, with body size evolution potentially interpreted as either fitting either a non-directional Brownian motion model or a stasis model. A Dispersal−Extinction−Cladogenesis analysis reconstructed the areas that are now South Africa and Europe as the ancestral areas of Rhynchosauria and Rhynchosauridae, respectively. The reconstruction of dispersal events between geographic areas that are broadly separated paleolatitudinally implies that barriers to the dispersal of rhynchosaurs from either side of the paleo-Equator during the Middle Triassic were either absent or permeable.